Estimating ski orientation using IMUs in alpine skiing - Chris Hummel; Andreas Huber; Peter Spitzenpfeil (Current Issues in Sport Science, 2024)
Ski-snow interaction is the essential component of alpine skiing. To understand how a skier manipulates his ski to turn, we need to develop methods to measure the orientation of the ski throughout a complete run. Recent studies tried to use IMUs to estimate edge angle (EA) during skiing.